Божа велич і провидіння в богослов’ї Іринея Ліонського - Zhukovskyy, Viktor (Vox Patrum, 2018)
The article discusses the problem of the ontological distinction between God’s transcendence and immanence in the theological thought of Irenaeus of Lyons, a Church Father of the II-III century. The author presents the main conceptual and terminological apparatus that Irenaeus used in his antinomic approach to the “reconciliation” of apophatic and kataphatic images of God. He analyzes the key characteristics of these two dimensions of the nature of God. Special attention is paid to the analysis of the kataphatic approache in answering the question: how can God, who is completely ontologicaly removed from created reality, be at the same time actively present in the world and filling it. In this context the author analyzes the key notions, which express the “intradivine” remoteness and God’s active nearness in relation to created being.